Development and verification of an open-source computational framework to simulate injection moulding - Fontaínhas, Ana Margarida Cunhal (2019)
Injection moulding is one of the most important processing techniques for thermoplastic materials, and due to the high competition and product requirements, it demands continuous optimization. In industrial practice, aiming to minimize the resources spent on the design and manufacturing activities, it is common to resort to appropriate computational modelling tools. However, mainly due to the typical high cost of proprietary software, the support of computational modelling tools in injection moulding design related tasks is not available to medium and small sized companies. This framework, and the clear perspective of the benefit brought by computational modelling, has been motivating the development of codes based on open-source libraries, as happens with OpenFOAM computational library. This work aims to identify the computational framework employed by injection moulding codes well established in industry, and perform the required adaptations on the most appropriate solvers to replicate it in OpenFOAM. Then a few case studies will be employed to compare the predictions and performance of the proprietary and open source codes